137k views
4 votes
Hey can you please help me posted picture of question

Hey can you please help me posted picture of question-example-1
User Stranac
by
5.8k points

1 Answer

5 votes
Vertex of the parabola: V=(4,-3)=(h,k)→h=4, k=-3
The parabola is vertical, then its equation has the form:
y=a(x-h)^2+k
y=a(x-4)^2+(-3)
y=a(x-4)^2-3

When the x-value is 5, the y-values is -6: x=5, y=-6
What is the coefficient of the squared expression in the parabola's equation: a=?

y=a(x-4)^2-3
x=5, y=-6→-6=a(5-4)^2-3
-6=a(1)^2-3
-6=a(1)-3
-6=a-3
-6+3=a-3+3
-3=a
a=-3

Answer: The coefficient of the squared expression in the parabola's equation is -3

Answer: Option D. -3
User Ed Ayers
by
5.8k points